Stainless steel powder, stainless steel member, and method for producing stainless steel member
By increasing the content of specific elements in the steel, especially Cr, Nb, Mo, W and Al, the problem of insufficient high-temperature oxidation resistance in the prior art is solved, and a significant improvement in high-temperature tensile strength and oxidation resistance is achieved, and the excellent performance of complex-shaped components is ensured.
Patent Information
- Application Number
- JP2023515759
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-02-17
- Filing Date
- 2022-12-01
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-12-01
AI Technical Summary
The prior art is difficult to achieve sufficient high-temperature oxidation resistance in components such as automotive exhaust systems and heat exchangers. Especially in high-temperature environments, SUS444 steel has insufficient high-temperature strength and poor material handling, making it difficult to manufacture complex-shaped components.
By increasing the content of Cr, Nb, Mo, W, Cu and Al, especially the content of Cr reaches 18.0% or more, the content of Nb reaches 0.50% or more, and adding Mo and W within a suitable range, ensuring (Mo+W) is ≥2.0%, while increasing the content of Al to improve the high-temperature oxidation resistance.
A significant improvement in high-temperature oxidation resistance is achieved, ensuring that the tensile strength of 0.2% at 800°C reaches 60 MPa or above, and the integrity of the oxide film is maintained during the 400-hour oxidation test, avoiding cracks in the material during the rapid curing process, and ensuring excellent shapeability of complex-shaped components.
Smart Images

Figure 0007658425000001 
Figure 0007658425000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a stainless steel powder, and in particular to a stainless steel powder suitable for producing components having complex shapes and requiring excellent high-temperature strength and oxidation resistance, such as automobile exhaust system components and heat exchangers. The present invention also relates to a stainless steel component shaped using the stainless steel powder and a method for producing the same. [Background technology]
[0002] In recent years, the use of metal additive manufacturing has become more widespread. The most widely used additive manufacturing method at present is the powder bed fusion method (also known as the powder bed method). The powder bed fusion method is an additive manufacturing method that uses a laser or electron beam as a heat source to melt the raw metal powder while additive manufacturing.
[0003] The greatest feature of additive manufacturing is that it can produce objects with shapes that were impossible to mold using conventional processing methods, taking into account the surface and internal structures. Furthermore, because additive manufacturing does not require consideration of the workability of the material, it can be used to mold any shape, even with materials such as Ni-based alloys and Ti-based alloys, which were previously difficult to process and had limited product shapes.
[0004] Taking advantage of these characteristics, the industrial use of metal additive manufacturing is progressing in the aerospace and medical fields. For example, for components with complex shapes and requiring high heat resistance, such as turbine blades, manufacturing Ni alloy components using additive manufacturing has the advantage of optimizing the shape and reducing the number of components. In the medical field, additive manufacturing is also being used due to its advantage of being able to manufacture artificial joints and implants with shapes adapted to each patient.
[0005] At present, additive manufacturing is limited to applications in the aerospace and medical fields due to its low mass-productivity and high manufacturing costs, but if these issues can be resolved, its application is expected to spread to fields such as automobiles where productivity and cost are important. In particular, in the automobile field, applying additive manufacturing to the manufacture of exhaust system components and heat exchangers with complex shapes may add value by optimizing the shape and improving the overall strength of the components by eliminating the need for joining such as brazing or welding. For this reason, Fe-based alloys such as stainless steel, which are cheaper than Ni-based alloys and Ti-based alloys, are attracting attention as materials to be used in additive manufacturing.
[0006] Patent documents 1 to 6 disclose stainless steel powders for additive manufacturing. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2019 / 139017 [Patent Document 2] International Publication No. 2019 / 235014 [Patent Document 3] International Publication No. 2020 / 110498 [Patent Document 4] International Publication No. 2021 / 214958 [Patent Document 5] Patent No. 6270563 [Patent Document 6] Patent No. 6985940 Summary of the Invention [Problem to be solved by the invention]
[0008] In recent years, there has been a demand for improved fuel efficiency and reduced carbon dioxide emissions, and the temperature of automobile exhaust gases is on the rise in response to these strict environmental regulations. In particular, components close to the engine, such as exhaust manifolds, may be exposed to high temperatures exceeding 1000°C. As a result, the SUS444 series steel (18mass%Cr-2mass%Mo-0.5mass%Nb), which has been used for high-temperature components up to now, is beginning to lack high-temperature strength. Therefore, there is a demand for stainless steels that have high-temperature strength that exceeds that of SUS444 and oxidation resistance that is equal to or better than that of SUS444.
[0009] In order to increase the high-temperature strength of stainless steel, it is effective to increase the content of elements such as Cr, Nb, Mo, W, Cu, and Al. In particular, Al has the effect of increasing not only high-temperature strength but also oxidation resistance. However, if the content of these elements is increased, the material strength increases excessively even at room temperature, making it difficult to manufacture stainless steel plates and stainless steel pipes. Even if stainless steel plates and stainless steel pipes can be manufactured, their low workability causes cracks during processing such as pressing and bending, and it is often impossible to obtain the desired shape for exhaust manifolds, heat exchangers, etc.
[0010] Therefore, the inventors focused on additive manufacturing as a method that enables high alloying and high performance of materials without being limited by manufacturability or processability. When additive manufacturing is performed using the powder bed method, metal powder is used as the material, but since metal powder is easier to manufacture than plate material or pipe material, the degree of freedom in component design is significantly increased. In addition, in the case of components with complex shapes such as exhaust manifolds and heat exchangers, molding the final product in one process by additive manufacturing can sometimes shorten the manufacturing period and also has a high degree of freedom in shape, rather than spending multiple processes to mold the components from plate material or pipe material. In this way, it was thought that by using additive manufacturing, it would be possible to achieve significant high functionality of automobile exhaust system components and heat exchangers.
[0011] Patent documents 1 to 6 disclose stainless steel powders for additive manufacturing. However, the materials disclosed in Patent documents 1 to 6 do not satisfy sufficient high-temperature strength and oxidation resistance required for application to automobile exhaust system components, particularly exhaust manifolds, and there has been a demand for the development of stainless steel powders that satisfy these required properties. Furthermore, components manufactured by additive manufacturing are required to be free of cracks even with the rapid solidification that is unique to additive manufacturing, that is, to have excellent formability.
[0012] The present invention has been made in view of the above circumstances, and has an object to provide a stainless steel powder that can be used to produce stainless steel parts having excellent high-temperature strength and oxidation resistance.
[0013] Here, excellent high-temperature yield strength means that the 0.2% yield strength measured by carrying out a tensile test at 800°C is 60 MPa or more.
[0014] In addition, excellent oxidation resistance means that the surface of a stainless steel member is polished with #600 abrasive paper, and after an oxidation test in which the specimen is held in air at 800°C for 400 hours, the oxidation weight gain is 20 g / m 2 This means that the oxide film is not peeled off and that the oxide film is not peeled off. [Means for solving the problem]
[0015] The present inventors have conducted extensive research to achieve the above object, and have found that excellent high-temperature strength and oxidation resistance can be achieved by increasing the Cr content to 18.0 mass% or more, containing 0.50 mass% or more, preferably 1.0 mass% or more, Cu to 0.7 mass% or more, and one or both of Mo and W to 2.0 mass% or more in total. Furthermore, they have found that even better high-temperature strength and oxidation resistance can be obtained by containing 0.3 mass% or more of Al. Furthermore, they have found that particularly excellent high-temperature strength and oxidation resistance can be obtained by increasing the Al content to 2.0 mass% or more.
[0016] It is difficult to process such high-alloy steel into plate or pipe material as in the conventional way, but by producing metal powder and using it as a material for additive manufacturing, it is possible to obtain stainless steel components with complex shapes and extremely excellent properties.
[0017] In particular, when considering application to exhaust manifolds, it is desirable for the steel to have excellent oxidation resistance and high-temperature yield strength superior to that of SUS 444. More specifically, it is desirable for the steel to have high-temperature yield strength such that the 0.2% yield strength at 800°C is 60 MPa or more.
[0018] The present invention has been completed based on the above findings and further investigations.
[0019] [1] In mass percent, C: 0.20% or less, Si: 2.0% or less, Mn: 2.0% or less, P: 0.040% or less, S: 0.010% or less, Cr: 18.0-35.0%, Ni: 1.0% or less, Cu: 0.50-4.0%, Nb: 0.7-3.0%, Mo: 6.0% or less W: 6.0% or less, N: 0.030% or less, A stainless steel powder containing 0.10% or less O, satisfying the following formula (1), with the remainder being Fe and unavoidable impurities: (Mo+W)≧2.0 (1) In the formula (1), Mo and W are the contents (mass%) of Mo and W, respectively. [2] The Cu content, in mass%, is The stainless steel powder according to [1], wherein Cu is 1.0 to 4.0%. [3] Furthermore, in mass percent: The stainless steel powder according to [1] or [2], containing Al: 6.0% or less. [4] Furthermore, in mass percent: Ti: 0.30% or less, V: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Zr: 0.50% or less, Ca: 0.0100% or less, Mg: 0.0050% or less, REM: 0.50% or less, Sn: 0.50% or less, Sb: 0.50% or less The stainless steel powder according to any one of [1] to [3], comprising one or more selected from the following: [5] In mass percent, C: 0.20% or less, Si: 2.0% or less, Mn: 2.0% or less, P: 0.040% or less, S: 0.010% or less, Cr: 18.0-35.0%, Ni: 1.0% or less, Cu: 0.50-4.0%, Nb: 0.7-3.0%, Mo: 6.0% or less W: 6.0% or less, N: 0.030% or less, A stainless steel member containing 0.10% or less O, satisfying the following formula (1), with the balance being Fe and unavoidable impurities: (Mo+W)≧2.0 (1) In the formula (1), Mo and W are the contents (mass%) of Mo and W, respectively. [6] The Cu content, in mass%, The stainless steel member according to [5], wherein Cu is 1.0 to 4.0%. [7] Furthermore, in mass percent: The stainless steel member according to [5] or [6], containing Al: 6.0% or less. [8] Furthermore, in mass percent: Ti: 0.30% or less, V: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Zr: 0.50% or less, Ca: 0.0100% or less, Mg: 0.0050% or less, REM: 0.50% or less, Sn: 0.50% or less, Sb: 0.50% or less The stainless steel member according to any one of [5] to [7], comprising one or more selected from the following: [9] A method for producing a stainless steel member, comprising: producing the stainless steel member by an additive manufacturing method using the stainless steel powder according to any one of [1] to [4] above. Effect of the Invention
[0020] According to the present invention, it is possible to provide a stainless steel powder that can be used to produce stainless steel members having excellent high-temperature strength and oxidation resistance.
[0021] According to the present invention, it is possible to provide a stainless steel powder that is preferably used for manufacturing stainless steel members, particularly for manufacturing stainless steel members by additive manufacturing. The stainless steel powder of the present invention is suitable as a material for stainless steel members that have complex shapes and require excellent heat resistance, such as automobile exhaust system members and heat exchangers, and is particularly suitable as a material when manufacturing the stainless steel members by additive manufacturing.
[0022] In addition, the stainless steel member produced using the stainless steel powder of the present invention has excellent high-temperature strength and oxidation resistance. Furthermore, it has excellent formability because cracks do not occur due to sudden temperature changes during additive manufacturing. The stainless steel member obtained by the present invention is particularly suitable as a member having a complex shape and requiring excellent heat resistance, such as an automobile exhaust system member or a heat exchanger. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention will be described based on the following embodiments.
[0024] First, the composition of the stainless steel powder and stainless steel member of the present invention will be described. Note that the unit of the composition is always "mass %", but hereinafter, unless otherwise specified, it will be simply represented as "%".
[0025] C: 0.20% or less C has the effect of forming carbides together with elements such as Nb to increase the strength of steel. To obtain this effect, the C content is preferably 0.0050% or more, and more preferably 0.03% or more. On the other hand, if the C content exceeds 0.20%, the steel becomes excessively hard, and the toughness of the stainless steel member decreases. Also, if the C content exceeds 0.20%, solidification cracking is likely to occur during additive manufacturing, and the moldability decreases. Therefore, the C content is set to 0.20% or less. The C content is preferably 0.15% or less.
[0026] Si: 2.0% or less Silicon has the effect of improving the oxidation resistance of steel. To obtain this effect, the Si content is preferably 0.01% or more. However, if the Si content exceeds 2.0%, the steel becomes excessively hard and the toughness decreases. Therefore, the Si content is set to 2.0% or less. The Si content is preferably 1.5% or less, and more preferably 1.0% or less.
[0027] Mn: 2.0% or less Mn has the effect of reducing the oxidation rate and preventing spalling of scale. To obtain this effect, the Mn content is preferably 0.01% or more. On the other hand, since Mn is an element that forms the austenite phase, if the Mn content exceeds 2.0%, the austenite phase forms and the thermal fatigue properties deteriorate. Therefore, the Mn content is set to 2.0% or less. The Mn content is preferably 1.0% or less.
[0028] P:0.040% or less Since P is an element that reduces corrosion resistance, it is desirable to reduce it, and the upper limit of the P content is set to 0.040%. The P content is preferably 0.030% or less, and more preferably 0.020% or less. The lower limit of the P content is not particularly limited. However, since excessive de-P leads to an increase in costs, the P content is preferably 0.005% or more.
[0029] S: 0.010% or less Since S is an element that reduces corrosion resistance, it is desirable to reduce the content, and the upper limit of the S content is set to 0.010%. The S content is preferably 0.005% or less, and more preferably 0.003% or less. The lower limit of the S content is not particularly limited. However, since excessive de-S leads to an increase in costs, the S content is preferably 0.0005% or more.
[0030] Cr: 18.0~35.0% Cr is an important element that improves the corrosion resistance and oxidation resistance of steel. In order to obtain the targeted excellent oxidation resistance equal to or better than that of SUS444, the Cr content must be 18.0% or more. However, if the Cr content exceeds 35.0%, the toughness of the stainless steel member decreases. Therefore, the Cr content is set to the range of 18.0 to 35.0%. The Cr content is preferably 20.0% or more, and more preferably 22.0% or more. Moreover, the Cr content is preferably 30.0% or less, and more preferably 27.0% or less.
[0031] Ni: 1.0% or less Ni has the effect of improving the toughness of stainless steel members. To obtain this effect, the Ni content is preferably 0.01% or more. On the other hand, Ni is an element that promotes the formation of the austenite phase. If the Ni content exceeds 1.0%, the austenite phase is formed, and the thermal fatigue properties and oxidation resistance are reduced. Therefore, the Ni content is set to 1.0% or less. The Ni content is preferably 0.5% or less.
[0032] Cu: 0.50-4.0% Cu is an element that precipitates in steel as ε-Cu and enhances high-temperature yield strength. This effect can be obtained by making the Cu content 0.50% or more, preferably 1.0% or more. However, if the Cu content exceeds 4.0%, the steel becomes excessively hard and the toughness of the stainless steel member decreases. Therefore, the Cu content is set to a range of 0.50 to 4.0%, preferably 1.0 to 4.0%. The Cu content is more preferably 1.5% or more. Also, the Cu content is preferably 3.0% or less.
[0033] Nb: 0.7-3.0% Nb has the effect of increasing the high-temperature yield strength of steel as a solid solution strengthening element. It also has the effect of increasing the high-temperature yield strength of steel by forming carbides and nitrides with C and N in the steel. These effects are obtained when the Nb content is 0.7% or more. However, when the Nb content exceeds 3.0%, an intermetallic compound phase is generated and the toughness of the stainless steel member decreases. Therefore, the Nb content is set to the range of 0.7 to 3.0%. The Nb content is preferably in the range of 0.7 to 2.0%, and more preferably in the range of 0.7 to 1.5%.
[0034] Mo: 6.0% or less, W: 6.0% or less, and satisfying the following formula (1): (Mo+W)≧2.0 (1) In the formula (1), Mo and W are the contents (mass%) of Mo and W, respectively. Mo and W have the effect of increasing the high temperature yield strength of steel as solid solution strengthening elements. In order to obtain this effect, it is necessary to contain one or two of Mo and W in total at 2.0% or more. In other words, it is necessary to satisfy the above formula (1). The total content of one or two of Mo and W is preferably 3.0% or more. On the other hand, if the content of Mo and W exceeds 6.0%, intermetallic compounds precipitate, which leads to a decrease in the toughness of the stainless steel member. Therefore, the content of Mo and W is 6.0% or less. The content of Mo and W is preferably 5.0% or less. For the same reason, it is preferable that the total content of one or two of Mo and W is 6.0% or less. The lower limit of each of the content of Mo and W is not particularly limited. The lower limit of each of the content of Mo and W may be 0 mass% as long as the above formula (1) is satisfied.
[0035] N: 0.030% or less N has the effect of increasing the strength of steel by forming nitrides with elements such as Nb. To obtain this effect, the N content is preferably 0.0030% or more, and more preferably 0.0050% or more. On the other hand, if the N content exceeds 0.030%, the toughness of the stainless steel member decreases. Therefore, the N content is set to 0.030% or less. The N content is preferably 0.020% or less.
[0036] O: 0.10% or less The stainless steel powder of the present invention can be produced by gas atomization or water atomization, but metal powders produced by these methods are prone to contamination with O. In order to reduce the amount of oxide-based inclusions formed in the shaped product, the O content is set to 0.10% or less. The O content is preferably 0.05% or less. There is no particular lower limit for the O content. However, since excessive de-O leads to increased costs, the O content is preferably 0.005% or more.
[0037] The ferritic stainless steel powder and stainless steel member of the present invention have a composition containing the above-mentioned components with the balance being Fe and unavoidable impurities.
[0038] The stainless steel powder and stainless steel member of the present invention may further contain Al: 6.0% or less in addition to the above-mentioned components.
[0039] Al: 6.0% or less Al is an element that acts as a deoxidizer. To achieve this effect, the Al content is preferably 0.001% or more. In addition, by further increasing the Al content, an Al oxide film is formed on the surface, which has the effect of significantly improving the oxidation resistance of the steel. To achieve this effect, the Al content is more preferably 0.3% or more, even more preferably 2.0% or more, even more preferably 3.0% or more, and particularly preferably 4.0% or more. However, if the Al content exceeds 6.0%, the toughness of the stainless steel member decreases. Furthermore, the linear expansion coefficient of the steel increases, and the thermal fatigue properties of the stainless steel member decrease. For this reason, the Al content is set to 6.0% or less.
[0040] In addition to the above components, the stainless steel powder and stainless steel part of the present invention may further contain one or more selected from Ti: 0.30% or less, V: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Zr: 0.50% or less, Ca: 0.0100% or less, Mg: 0.0050% or less, REM: 0.50% or less, Sn: 0.50% or less, and Sb: 0.50% or less.
[0041] Ti: 0.30% or less Ti has the effect of forming carbides and nitrides with C and N in steel to increase the strength of steel. To obtain this effect, the Ti content is preferably 0.01% or more. However, if the Ti content exceeds 0.30%, the steel becomes excessively hard and the toughness of the stainless steel member decreases. Therefore, when Ti is contained, the Ti content is set to a range of 0.30% or less. The Ti content is preferably 0.20% or less.
[0042] V: 0.50% or less V has the effect of increasing the strength of steel by forming carbides and nitrides with C and N in the steel. To obtain this effect, the V content is preferably 0.01% or more. However, if the V content exceeds 0.50%, the steel becomes excessively hard and the toughness of the stainless steel member decreases. Therefore, when V is contained, the V content is set to a range of 0.50% or less. The V content is preferably 0.30% or less.
[0043] Co:0.50% or less Co is an element that improves the toughness of stainless steel members. To obtain this effect, the Co content is preferably 0.01% or more. However, if the Co content exceeds 0.50%, the steel becomes excessively hard and the toughness decreases. Therefore, if Co is contained, the Co content is set to 0.50% or less.
[0044] B: 0.0100% or less B has the effect of strengthening grain boundaries and improving toughness. To obtain this effect, the B content is preferably 0.0002% or more. However, if the B content exceeds 0.0100%, the steel becomes excessively hard, and the toughness of the stainless steel member decreases. Therefore, when B is contained, the B content is set to a range of 0.0100% or less. The B content is more preferably 0.0005% or more. Furthermore, the B content is more preferably 0.0050% or less.
[0045] Zr: 0.50% or less Zr has the effect of improving the adhesion of the oxide film and enhancing the oxidation resistance. To obtain this effect, the Zr content is preferably 0.01% or more. However, if the Zr content exceeds 0.50%, an intermetallic compound phase precipitates, which reduces the oxidation resistance. Therefore, when Zr is contained, the Zr content is set to 0.50% or less. The Zr content is preferably 0.30% or less, and more preferably 0.10% or less.
[0046] Ca:0.0100% or less Ca has the effect of lowering the melting point of oxide-based inclusions and reducing the number of inclusions in molten steel when producing metal powder. In order to obtain this effect, the Ca content is preferably 0.0002% or more. However, if the Ca content exceeds 0.0100%, the toughness of the stainless steel member decreases. Therefore, when Ca is contained, the Ca content is set to a range of 0.0100% or less. The Ca content is more preferably 0.0005% or more. Moreover, the Ca content is preferably 0.0050% or less, more preferably 0.0030% or less.
[0047] Mg: 0.0050% or less Mg is an element that has the effect of improving corrosion resistance. This effect is obtained when the Mg content is 0.0002% or more. Therefore, when Mg is contained, the Mg content is preferably in the range of 0.0002% or more. However, when the Mg content exceeds 0.0050%, the toughness of the stainless steel member decreases. Therefore, when Mg is contained, the Mg content is set to be in the range of 0.0050% or less. The Mg content is more preferably 0.0005% or more. Moreover, the Mg content is preferably 0.0035% or less, more preferably 0.0020% or less.
[0048] REM: 0.50% or less REM (rare earth elements) have the effect of improving the adhesion of oxide films and enhancing oxidation resistance. To obtain this effect, the REM content is preferably 0.01% or more. However, if the REM content exceeds 0.50%, the toughness of the stainless steel member decreases. Therefore, when REM is contained, the REM content is set to a range of 0.50% or less. The REM content is more preferably 0.05% or more, and further preferably 0.10% or more. In addition, the REM content is preferably 0.30% or less, and more preferably 0.20% or less. Note that REM is a collective term for 15 elements including Sc, Y, and lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71, and the REM content here is the total content of these elements.
[0049] Sn: 0.50% or less Sn has the effect of preventing roughness when the surface of a molded object is polished. To obtain this effect, the Sn content is preferably 0.01% or more. However, if the Sn content exceeds 0.50%, solidification cracking is likely to occur, and moldability is reduced. Therefore, when Sn is contained, the Sn content is set to a range of 0.50% or less. The Sn content is more preferably 0.03% or more, and further preferably 0.05% or more. Moreover, the Sn content is preferably 0.30% or less, and more preferably 0.10% or less.
[0050] Sb: 0.50% or less Sb has the effect of preventing roughness when the surface of a molded object is polished. To obtain this effect, the Sb content is preferably 0.01% or more. However, if the Sb content exceeds 0.50%, solidification cracking is likely to occur, and moldability is reduced. Therefore, when Sb is contained, the Sb content is set to a range of 0.50% or less. The Sb content is more preferably 0.03% or more, and further preferably 0.05% or more. Moreover, the Sb content is preferably 0.30% or less, and more preferably 0.10% or less.
[0051] Next, the preferred properties (particle size) of the stainless steel powder of the present invention will be described.
[0052] The stainless steel powder of the present invention has a volume-based median diameter D 50 The median diameter D of the stainless steel powder is preferably 10 μm or more and 200 μm or less. 50 If the median diameter D of the stainless steel powder is too small, the powder will have a reduced fluidity, resulting in uneven powder packing, which may cause defects such as voids during additive manufacturing. As a result, the strength, low-temperature toughness, and corrosion resistance of the steel member manufactured using such steel powder as a raw material may be reduced. 50 When the median diameter D of the stainless steel powder is 10 μm or more, it is easy to suppress the generation of defects such as voids during additive manufacturing. 50 The median diameter D of the stainless steel powder is preferably 10 μm or more. 50is more preferably 20 μm or more, and further preferably 30 μm or more. On the other hand, the median diameter D 50 If the median diameter D of the stainless steel powder is excessively large, it may cause defects such as voids during additive manufacturing. As a result, in a steel member manufactured using such a steel powder as a raw material, the defects may lead to a decrease in strength, low-temperature toughness, and corrosion resistance. 50 When the median diameter D of the stainless steel powder is 200 μm or less, it is easy to suppress the generation of defects such as voids during additive manufacturing. 50 The median diameter D of the stainless steel powder is preferably 200 μm or less. 50 is more preferably 150 μm or less, and further preferably 100 μm or less.
[0053] The median diameter of the stainless steel powder is D 50 refers to the median diameter (50% particle diameter) of the cumulative volume distribution of the stainless steel powder. A laser diffraction particle size measuring device can be used to measure the median diameter of the stainless steel powder. In the present invention, the median diameter D 50 Measure.
[0054] Examples of laser diffraction particle size measuring devices include the LA-950V2 manufactured by Horiba, Ltd. Of course, other devices may be used, but it is preferable to use a device with a measurable particle size range with a lower limit of 0.1 μm or less and an upper limit of 200 μm or more in order to perform accurate measurements. In the laser diffraction particle size measuring device, a laser beam is irradiated onto a solvent in which stainless steel powder is dispersed, and the particle size distribution and average particle size (median size) of the stainless steel powder are measured from the diffraction and scattering intensity of the laser beam. As a solvent for dispersing stainless steel powder, it is preferable to use ethanol, which has good dispersibility of the powder and is easy to handle. If a solvent such as water, which has high van der Waals forces and low dispersibility, is used, the powder may aggregate during measurement, resulting in a measurement result that is larger than the original average particle size, which is not preferable. Therefore, it is preferable to subject the ethanol solution containing stainless steel powder to an ultrasonic dispersion treatment before measurement.
[0055] Since the appropriate dispersion treatment time differs depending on the stainless steel powder to be measured, the dispersion treatment time is set to seven stages at 10-minute intervals between 0 and 60 minutes, and the particle size distribution and average particle diameter (median diameter) of the stainless steel powder are measured after each dispersion treatment. During each measurement, the solvent is stirred to prevent the stainless steel powder from agglomerating. The smallest average particle diameter (median diameter) obtained in seven measurements performed with the dispersion treatment time changed at 10-minute intervals is taken as the median diameter D of the stainless steel powder. 50 Used as.
[0056] Next, a preferred embodiment of the method for producing stainless steel powder of the present invention will be described.
[0057] The stainless steel powder of the present invention is provided in the final material form through the following series of manufacturing steps: for example, melting, forming an ingot, remelting the master ingot, and producing powder through an atomization process.
[0058] First, in the melting-ingot formation process, a predetermined amount of the above-mentioned elements is melted as materials in a high-frequency vacuum melting furnace, alloyed, and cast to produce an ingot (master ingot). At this time, it is preferable to melt under the conditions of a reduced pressure Ar atmosphere and a melting temperature of 1600°C or higher. The reason for setting these conditions is as follows. If the melting temperature is too low, the molten steel will solidify and clog the nozzle when it is dropped from the nozzle. In addition, from the viewpoint of preventing oxidation of the molten steel, it is preferable to melt in a reduced pressure Ar atmosphere. Note that the melting furnace used in this process is not limited to a high-frequency vacuum melting furnace, and other melting furnaces (for example, a direct current heating type melting furnace) can also be used in the present invention.
[0059] Next, in the master ingot remelting-atomization process, the cast master ingot is used as the material to remelt in a melting furnace such as a high-frequency or induction furnace, and stainless steel powder with a low oxygen content is obtained by gas atomization using inert gases such as Ar or He.
[0060] These stainless steel powders are then preferably milled to a diameter of about 100 mm or less having a median diameter D 50 The stainless steel powder is then classified so that the powder has a diameter of 100 mm or less, and is used as the stainless steel powder of the present invention. The classification may be performed using a sieve or other methods such as air flow classification. Moreover, water atomization may be used instead of gas atomization.
[0061] Next, one embodiment of the method for producing a stainless steel member of the present invention will be described.
[0062] First, the stainless steel powder of the present invention is used as a material to form a stainless steel laminated object (three-dimensional structure) by, for example, an additive manufacturing method (metal powder additive manufacturing method). For example, a 3D printer method can be used as the additive manufacturing method. Here, a laser-type powder bed type 3D printer is used. The setting conditions of the 3D printer are not specified. From the viewpoint of preventing excessive melting or insufficient melting, for example, it is preferable that the laser output of the 3D printer is 150 to 300 W and the scan speed is 700 to 1100 mm / s. Next, the molded member is subjected to heat treatment as necessary to obtain the stainless steel member of the present invention. In this heat treatment step, the stainless steel member is held at a temperature in the range of 850 to 1200 ° C for 1 minute or more, and then air-cooled. Preferably, the stainless steel member is held at a temperature in the range of 1000 to 1200 ° C for 10 minutes or more, and then air-cooled. EXAMPLES
[0063] The present invention will be described below with reference to examples. First, raw material powders having the component compositions A to K shown in Table 1 were produced by a gas atomization method. The produced powders were then classified to measure the volume-based median diameter D 50A stainless steel powder was obtained in which the value of was adjusted to be the value shown in Table 1. This was used as the material to manufacture stainless steel members (steel members A to K) by the powder bed method. The molding device used was an M290 manufactured by EOS. The heat source for melting the stainless steel powder was a laser, and molding was performed under conditions of a scanning speed of 800 m / s, an output of 200 W, and a powder layer thickness of 40 μm per layer. The shape of the molded object was a plate shape with a width of 35 mm, a length of 180 mm, and a thickness of 4 mm in the layering direction. This molded object was subjected to a heat treatment in which it was held in the atmosphere at 1000°C for 1 hour and then air-cooled, and then test pieces were taken for each test described later and their characteristics were evaluated. The steel powder K has a composition equivalent to that of SUS 444. Sample L is a hot-rolled annealed sheet having a composition equivalent to that of SUS 444 and having a thickness of 4 mm, which is produced by conventional small steel ingot melting, hot rolling and hot-rolled sheet annealing.
[0064] (1) Formability The moldability was evaluated based on the presence or absence of cracks in the stainless steel members (steel members A to K) after additive manufacturing. First, the surfaces of the heat-treated molded objects (the two largest surfaces) were ground to a thickness of 1 mm. Penetrant testing was performed on these ground surfaces in accordance with the method described in JIS Z2343-1 (2017) to confirm the presence or absence of cracks. If no cracks of 1.0 mm or more in length were found, the sample was rated as ◯, and if cracks of 1.0 mm or more in length were found, the sample was rated as ×. If the sample was ◯, the sample was rated as having excellent formability.
[0065] (2) High temperature resistance The high temperature yield strength is the 0.2% yield strength (σ 0.2 From the heat-treated shaped objects (steel members A to K) or the hot-rolled annealed sheet (steel sheet L), plate-shaped tensile test pieces with a thickness of 4 mm, a parallel part width of 10 mm, and a rating distance of 50 mm were taken and held at a test temperature of 800°C for 15 minutes, after which a tensile test was carried out to determine the 0.2% yield strength. At this time, the tensile speed was 0.2 mm / min. The measurement results of 0.2% yield strength were evaluated as follows: less than 60 MPa was x, 60 MPa to less than 100 MPa was ◯, and 100 MPa or more was ◎. ◯ or ◎ was evaluated as excellent high-temperature yield strength.
[0066] (3) Oxidation resistance The oxidation resistance was evaluated by carrying out an oxidation test. First, the surface (the two widest surfaces) of the heat-treated shaped object (steel members A to K) or the hot-rolled annealed sheet (steel sheet L) was ground by a thickness of 1 mm to obtain a plate-shaped test piece with a thickness of 2 mm. From this test piece, an oxidation test piece of 20 mm x 30 mm x 2.0 mm was taken, and the surface was polished with #600 abrasive paper to obtain an oxidation test piece. An oxidation test was carried out on this oxidation test piece by holding it in high-temperature air for 400 hours, and the oxidation resistance was evaluated. The test temperatures were 800°C and 1100°C. After the oxidation test, the oxidation weight gain was 20 g / m 2 If the oxidation increase exceeds 20g / m or peeling occurs on the surface oxide film, it is considered a failure (×). 2 If the test piece had a thickness of 0.1 mm or less and no peeling of the oxide film occurred, the test piece was rated as "pass" (◯). For oxidation resistance, a material was rated as × if it failed both the 800°C and 1100°C tests, as ◯ if it passed the 800°C test and failed the 1100°C test, and as ◎ if it passed both the 800°C and 1100°C tests. A rating of ○ or ◎ was used to evaluate the material as having excellent oxidation resistance.
[0067] The evaluation results of (1) to (3) above are shown in Table 2. It can be seen that within the range of the present invention, the material has excellent high-temperature strength and oxidation resistance, as well as excellent formability. In particular, the steel members E to I, which were manufactured using steel powder containing Al, passed the oxidation resistance test at 1100°C and had superior oxidation resistance.
[0068] [Table 1]
[0069] [Table 2] [Industrial Applicability]
[0070] By using the stainless steel powder of the present invention, it is possible to form stainless steel members having excellent high-temperature strength and oxidation resistance without solidification cracking. The stainless steel members obtained by the present invention can be suitably used in particular for heat exchangers and exhaust system members of automobiles. Furthermore, they can be applied to various members in addition to these uses.
Claims
1. In mass percent, C: 0.20% or less, Si: 2.0% or less, Mn: 2.0% or less, P: 0.040% or less, S: 0.010% or less, Cr: 18.0-35.0%, Ni: 1.0% or less, Cu: 0.50 to 4.0%, Nb: 0.7-3.0%, Mo: 6.0% or less, W: 6.0% or less, N: 0.030% or less, O: 0.10% or less, and has a component composition that satisfies the following formula (1), with the balance being Fe and unavoidable impurities; Volume-based median diameter D 50 The stainless steel powder has a particle size of 10 μm or more and 200 μm or less. (Mo+W)≧2.0...(1) Here, Mo and W in formula (1) are the contents (mass%) of Mo and W, respectively.
2. The Cu content is, in mass%, The stainless steel powder according to claim 1, wherein Cu is 1.0 to 4.0%.
3. Further, in mass%, The stainless steel powder according to claim 1, containing Al: 6.0% or less.
4. Further, in mass%, The stainless steel powder according to claim 2, containing Al: 6.0% or less.
5. Further, in mass%, Ti: 0.30% or less, V: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Zr: 0.50% or less, Ca: 0.0100% or less, Mg: 0.0050% or less, REM: 0.50% or less, Sn: 0.50% or less, Sb: 0.50% or less The stainless steel powder according to any one of claims 1 to 4, comprising one or more selected from the following:
6. In mass percent, C: 0.20% or less, Si: 2.0% or less, Mn: 2.0% or less, P: 0.040% or less, S: 0.010% or less, Cr: 18.0-35.0%, Ni: 1.0% or less, Cu: 0.50 to 4.0%, Nb: 0.85-3.0%, Mo: 6.0% or less, W: 6.0% or less, N: 0.030% or less, O: 0.10% or less, and has a component composition that satisfies the following formula (1), with the balance being Fe and unavoidable impurities; A high-temperature yield strength of 60 MPa or more as measured by a tensile test at 800 ° C. The surface of the test piece was polished with #600 abrasive paper, and an oxidation test was performed in which the test piece was held in air at 800°C for 400 hours. After that, the oxidation weight gain was 20g / m 2 A stainless steel member having oxidation resistance of 0.1 to 100% by weight and no peeling of the oxide film. (Mo+W)≧2.0...(1) Here, Mo and W in formula (1) are the contents (mass%) of Mo and W, respectively.
7. The Cu content is, in mass%, The stainless steel member according to claim 6, wherein Cu is 1.0 to 4.0%.
8. Further, in mass%, The stainless steel member according to claim 6, containing Al: 6.0% or less.
9. Further, in mass%, The stainless steel member according to claim 7, containing Al: 6.0% or less.
10. Further, in mass%, Ti: 0.30% or less, V: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Zr: 0.50% or less, Ca: 0.0100% or less, Mg: 0.0050% or less, REM: 0.50% or less, Sn: 0.50% or less, Sb: 0.50% or less The stainless steel member according to any one of claims 6 to 9, comprising at least one selected from the following:
11. A method for producing a stainless steel part by an additive manufacturing method using the stainless steel powder according to any one of claims 1 to 4, the method comprising the steps of: a high-temperature yield strength of 60 MPa or more as measured by a tensile test at 800°C; and a test piece obtained by polishing the surface with #600 abrasive paper is subjected to an oxidation test in which the test piece is held in air at 800°C for 400 hours, after which the oxidation weight gain is 20 g / m2 or less and no peeling of the oxide film occurs.
12. A method for producing a stainless steel part by an additive manufacturing method using the stainless steel powder according to claim 5, the method comprising the steps of: a high-temperature yield strength of 60 MPa or more as measured by a tensile test at 800°C; and a test piece obtained by polishing the surface with #600 abrasive paper is subjected to an oxidation test in which the test piece is held in air at 800°C for 400 hours, after which the oxidation weight gain is 20 g / m2 or less and no peeling of the oxide film occurs.
Citation Information
Patent Citations
Coating method for ceramic
JP1987070563A
Highly oxidation-resistant ferrite stainless steel plate
JP2012117084A
Ferritic stainless steel and manufacturing method therefor
JP2017150016A
Stainless steel powder for molding
JP2019119913A
Metal wire for welded and laminated shaping with metal 3D printer
JP2020158842A